Coating material set, coated film formation method and laminate
Patent Information
- Application Number
- JP2024211947
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-05-25
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-05-24
AI Technical Summary
【0008】 本発明によれば、鱗片状粒子の偏りが生じにくく、模様のバランス(配置)が良好であり、アクセント模様による多彩感を有し、かつ色味にムラの少ない統一感のある意匠を呈する美観性に優れた被膜を形成することができる。
Smart Images

Figure 2025026532000001 
Figure 2025026532000002 
Figure 2025026532000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel dressing set and the like. [Background technology]
[0002] Conventionally, decorative finishing methods that impart the aesthetic appearance of natural stone to buildings and civil engineering structures have been known. In recent years, there have been an increasing number of cases where decorative finishing with design features such as the diverse colors unique to natural stone is desired. As one such method, for example, Patent Document 1 describes a method in which a resin containing a mixture of colored mica (scale-like particles) of multiple colors is applied onto a base material. The use of scale-like particles in this way is also advantageous in terms of thinning and weight reduction of the formed coating. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-262134 Summary of the Invention [Problem to be solved by the invention]
[0004] However, when a coating material containing a combination of multiple colors of scale-like particles is applied as in Patent Document 1, there is a risk of unevenness in the pattern and color formed due to partial overlap, dense areas, or sparse areas between the scale-like particles.
[0005] The present invention has been made in consideration of the above-mentioned points, and has an object to provide a coating material that is capable of forming, by a simple method, a coating that is less likely to have biased patterns of scale-like particles and that presents a unified design with little unevenness in pattern and color, and has excellent aesthetics. [Means for solving the problem]
[0006] Means of the Invention As a result of intensive research into solving the above problems, the present inventors came up with the idea of a coating material set comprising at least two specific coating materials, and completed the present invention.
[0007] That is, the present invention has the following features. 1. A coating material set for forming a laminated coating, the coating material set including at least a first coating material and a second coating material, the first coating material being a coating material that forms a base layer, the second coating material being a coating material that includes a resin component and colored particles and that forms a design layer, The colored particles are scaly particles, The scale-like particles include large particles (L) having a short diameter of more than 2 mm, medium particles (M) having a short diameter of more than 0.7 mm and 2 mm or less, and small particles (S) having a short diameter of 0.7 mm or less, The colored particles include base color scale-like particles and accent color scale-like particles, The base color scaly particles are the color that is contained most in the colored particles, and the content of the base color scaly particles in the colored particles is 40 to 95% by weight. the accent color scale-like particles are of one or more colors different from the base color scale-like particles, and the content of the accent color scale-like particles is 5 to 60% by weight in the colored particles; a color difference (ΔE) between the base layer and the base-colored scaly particles is 1.0 to 10; A coating material set, wherein the color difference (ΔE) between the base color scale-like particles and the accent color scale-like particles is 2.5 or more. 2. A composition characterized in that the weight ratio of the medium particles (M) and small particles (S) to the large particles (L), [(M)+(S)] / (L), is 1 or more and 50 or less. 1. A coating material set according to claim 1. 3. A coating forming method for applying a first coating material and a second coating material to a substrate in this order, the first coating material being a coating material that forms a base layer, the second coating material being a coating material that contains a resin component and colored particles and that forms a design layer, The colored particles are scaly particles, The scale-like particles include large particles (L) having a short diameter of more than 2 mm, medium particles (M) having a short diameter of more than 0.7 mm and 2 mm or less, and small particles (S) having a short diameter of 0.7 mm or less, The colored particles include base color scale-like particles and accent color scale-like particles, The base color scaly particles are the color that is contained most in the colored particles, and the content of the base color scaly particles in the colored particles is 40 to 95% by weight. the accent color scale-like particles are of one or more colors different from the base color scale-like particles, and the content of the accent color scale-like particles is 5 to 60% by weight in the colored particles; a color difference (ΔE) between the base layer and the base-colored scaly particles is 1.0 to 10; The coating forming method is characterized in that the color difference (ΔE) between the base color scale-like particles and the accent color scale-like particles is 2.5 or more. 4. The method for forming a coating according to 3, characterized in that the weight ratio [(M)+(S)] / (L) of the medium particles (M) and small particles (S) to the large particles (L) is 1 or more and 50 or less. 5. A laminate comprising a base layer and a design layer laminated in this order on a substrate, the base layer being formed from a first coating material, and the design layer being formed from a second coating material containing a resin component and colored particles, The colored particles are scaly particles, The scale-like particles include large particles (L) having a short diameter of more than 2 mm, medium particles (M) having a short diameter of more than 0.7 mm and 2 mm or less, and small particles (S) having a short diameter of 0.7 mm or less, The colored particles include base color scale-like particles and accent color scale-like particles, The base color scaly particles are the color that is contained most in the colored particles, and the content of the base color scaly particles in the colored particles is 40 to 95% by weight. the accent color scale-like particles are of one or more colors different from the base color scale-like particles, and the content of the accent color scale-like particles is 5 to 60% by weight in the colored particles; a color difference (ΔE) between the base layer and the base-colored scaly particles is 1.0 to 10; A laminate characterized in that the color difference (ΔE) between the base color scale-like particles and the accent color scale-like particles is 2.5 or more. 6. A composition characterized in that the weight ratio [(M)+(S)] / (L) of the medium particles (M) and small particles (S) to the large particles (L) is 1 or more and 50 or less. 5. The laminate according to claim 1. Effect of the Invention
[0008] According to the present invention, it is possible to form a coating having excellent aesthetics, in which the scale-like particles are less likely to become unevenly distributed, the pattern has a good balance (arrangement), and the accent patterns give a sense of variety, while also presenting a unified design with little unevenness in color. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described.
[0010] The present invention relates to a coating material set for forming a laminate coating, characterized in that it comprises at least a first coating material and a second coating material.
[0011] <First covering material> The first coating material of the present invention is a coating material that forms a base layer. The first coating material preferably contains at least a resin component (A) and a color pigment (B). The resin component (A) (hereinafter also referred to as "component (A)") is not particularly limited, but is preferably at least one selected from water-soluble resins and water-dispersible resins (resin emulsions). Examples of the resin include vinyl acetate resins, polyester resins, alkyd resins, vinyl chloride resins, epoxy resins, acrylic resins, urethane resins, acrylic silicone resins, fluororesins, and the like, or composites thereof. These can be used alone or in combination of two or more. In the present invention, acrylic resins and acrylic silicone resins are preferred. These components (A) may also have crosslinking reactivity. When a component (A) having crosslinking reactivity is used, the water resistance, weather resistance, chemical resistance, and the like of the coating can be improved.
[0012] In the present invention, acrylic resin is particularly suitable as component (A). Acrylic resin is a resin in which (meth)acrylic acid alkyl ester is the main component of the resin skeleton, and other monomers are copolymerized as necessary. In the present invention, acrylic acid alkyl ester and methacrylic acid alkyl ester are collectively referred to as (meth)acrylic acid alkyl ester. Moreover, a monomer is a general term for a compound having a polymerizable unsaturated double bond.
[0013] Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, cyclohexyl (meth)acrylate, and the like. One or more of these can be used.
[0014] Specific examples of other monomers include, for example, Aromatic monomers such as styrene, 2-methylstyrene, vinyltoluene, t-butylstyrene, chlorostyrene, vinylanisole, vinylnaphthalene, divinylbenzene, phenyl (meth)acrylate, and benzyl (meth)acrylate; Nitrile group-containing monomers such as (meth)acrylonitrile, vinylidene cyanide, and α-cyanoethyl (meth)acrylate; Amide group-containing monomers such as maleic acid amide, (meth)acrylamide, N-monoalkyl (meth)acrylamide, N,N-dialkyl (meth)acrylamide, 2-(dimethylamino)ethyl (methacrylate), N-[3-(dimethylamino)propyl] (meth)acrylamide, and vinylamide; Carbonyl group-containing monomers such as acrolein, diacetone (meth)acrylamide, vinyl methyl ketone, vinyl ethyl ketone, and vinyl butyl ketone;
[0015] Carboxyl group-containing monomers such as (meth)acrylic acid, crotonic acid, maleic acid, itaconic acid, fumaric acid, isocrotonic acid, and salicylic acid; Amino group-containing monomers such as aminomethyl acrylate, aminoethyl acrylate, aminopropyl (meth)acrylate, amino-n-butyl (meth)acrylate, butylvinylbenzylamine, vinylphenylamine, p-aminostyrene, N-methylaminoethyl (meth)acrylate, and Nt-butylaminoethyl (meth)acrylate; Epoxy group-containing monomers such as glycidyl (meth)acrylate, diglycidyl fumarate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxyvinylcyclohexane, allyl glycidyl ether, ε-caprolactone-modified glycidyl (meth)acrylate, and β-methylglycidyl (meth)acrylate; Hydroxyl group-containing monomers such as hydroxypropyl (meth)acrylate, ethylene glycol mono(meth)acrylate, and glycerol mono(meth)acrylate; vinylidene halide monomers such as vinylidene fluoride; Alkoxysilyl group-containing monomers, such as vinyltrimethoxysilane, vinyltriethoxysilane, γ-(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, and γ-(meth)acryloyloxypropylmethyldimethoxysilane; Examples of the vinyl ether include ethylene, propylene, isoprene, butadiene, vinyl ether, vinyl ketone, etc. These may be used alone or in combination of two or more.
[0016] When the above-mentioned alkoxysilyl group-containing monomer is used as the other monomer, an acrylic silicone resin can be obtained.
[0017] The component (A) can be produced by emulsion polymerization of a monomer group obtained by appropriately mixing the above-mentioned monomers. Any known method can be used as the polymerization method, and in addition to normal emulsion polymerization, soap-free emulsion polymerization, feed emulsion polymerization, seed emulsion polymerization, etc. can also be used. During polymerization, an emulsifier, initiator, dispersant, polymerization inhibitor, polymerization retarder, buffer, chain transfer agent, etc. can be used.
[0018] As the emulsifier, various surfactants that can be used in emulsion polymerization can be used, and these may be reactive types (reactive surfactants) having polymerizable unsaturated double bonds. As the emulsifier, anionic surfactants and nonionic surfactants may be used alone or in combination.
[0019] The glass transition temperature (hereinafter simply referred to as "Tg") of the component (A) is preferably set to -50°C to 50°C. If Tg is within this range, the effects of the present invention can be stably obtained. In the present invention, Tg is a value calculated by Fox's formula. In addition, the average particle size of the component (A) is preferably 300 nm or less (more preferably 20 to 200 nm). If the average particle size is within this range, the water resistance, weather resistance, chemical resistance, etc. of the coating can be improved. In addition, the average particle size referred to here is a value measured by dynamic light scattering.
[0020] The color pigment (B) (hereinafter also referred to as "component (B)") is a component that imparts color, hiding power, etc. to the first coating material. Examples of component (B) include inorganic chromatic pigments such as ferric oxide (red oxide), yellow iron oxide, ultramarine, and cobalt green; organic chromatic pigments such as azo, naphthol, pyrazolone, anthraquinone, perylene, quinacridone, disazo, isoindolinone, benzimidazole, phthalocyanine, and quinophthalone; black pigments such as carbon black, iron-manganese composite oxide, iron-copper-manganese composite oxide, iron-chromium-cobalt composite oxide, copper-chromium composite oxide, copper-manganese-chromium composite oxide, and black iron oxide; white pigments such as titanium oxide, zinc oxide, and alumina; and other luster pigments (pearl pigments, aluminum pigments, metallic pigments, etc.), phosphorescent pigments, and fluorescent pigments. These can be used alone or in combination of two or more. The average particle size of the component (B) is preferably 1 μm or less, and more preferably 0.01 to 0.9 μm. The average particle size of the color pigment is measured by a laser diffraction particle size distribution measuring device. In the present invention, "α to β" is synonymous with "α or more and β or less."
[0021] The component (B) is preferably contained in an amount of 3 to 300 parts by weight (more preferably 5 to 250 parts by weight) per 100 parts by weight of the solid content of the component (A). With the component (B) in such a ratio, the first covering material (base layer) can be colored in a desired color, and the aesthetic appearance can be improved.
[0022] Furthermore, the first coating material preferably contains a powder component other than the color pigment (hereinafter also referred to as "component (C)"). Examples of such component (C) include heavy calcium carbonate, light calcium carbonate, kaolin, clay, china clay, diatomaceous earth, hydrous fine powdered silicic acid, talc, mica, barite powder, barium sulfate, precipitated barium sulfate, barium carbonate, magnesium carbonate, silica powder, aluminum hydroxide, and other extender pigments; silica particles, kansui stone, diatomaceous earth, silica stone, silica sand, gravel, glass beads, resin beads, metal particles, or powders and granules such as crushed rocks, glass, ceramics, shells, sintered bodies, concrete, mortar, plastics, rubber, and the like. These may be colored. These can be used alone or in combination of two or more.
[0023] In addition, the particle diameter of the component (C) is preferably 1 to 1000 μm (more preferably 5 to 850 μm, and even more preferably 10 to 600 μm). In addition, for example, when the powdery or granular material (C1) having a particle diameter of 53 to 300 μm is contained in the total amount of the component (C), preferably 40% by weight or more (more preferably 45% by weight or more, and even more preferably 50% by weight or more), a coating having even more excellent aesthetic appearance can be formed. The upper limit is preferably 100% by weight or less (more preferably 95% by weight or less, and even more preferably 90% by weight or less). Such an embodiment is more preferable in terms of improving the effects of the present invention. In addition, when the particle diameter of the component (C) is more than 20 μm, it can be measured by sieving using a metal mesh sieve specified in JIS Z8801-1:2000. In addition, when it is 20 μm or less, it can be measured using a laser diffraction type particle size distribution measuring device.
[0024] The (C) component is preferably contained in an amount of 10 to 600 parts by weight (more preferably 30 to 500 parts by weight, and even more preferably 50 to 400 parts by weight) per 100 parts by weight of the solid content of the (A) component. By containing the (C) component in such a ratio, a base layer having a more excellent aesthetic appearance can be formed. Furthermore, by containing the powder particles (C1) having a particle diameter of 53 to 300 μm, it is possible to form fine irregularities derived from the (C1) component on the surface of the base layer. This makes it easier to visually recognize the color as a uniform color, and further enhances the effects of the present invention. Furthermore, it is possible to suppress roughness caused by the jumping up of the ends of the scale-like particles in the design layer.
[0025] The first coating material can be produced by uniformly mixing the above-mentioned components by a known method, but if necessary, other components that can be used in normal coating materials can also be mixed in. Examples of such components include pigment dispersants, emulsifiers, thickeners, film-forming assistants, leveling agents, coupling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, dryness adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, defoamers, adsorbents, deodorizers, fibers, ultraviolet absorbers, light stabilizers, antioxidants, catalysts, crosslinking agents, etc.
[0026] <Second covering material> The second coating material of the present invention is a coating material that forms a design layer, and is characterized by containing a resin component (A) and colored particles (D).
[0027] The resin component (A) in the second coating material is not particularly limited, and may be selected from the same resins as the component (A) in the first coating material. These may be used alone or in combination of two or more.
[0028] The colored particles (D) (hereinafter referred to as "component (D)") impart design properties. The present invention is characterized in that component (D) contains base color scale-like particles (d1) and accent particles (d3). This results in an accent pattern in which accent particles (d3) are scattered within a base pattern formed by the base color scale-like particles (d1), and a design layer with a uniform feel and little unevenness in the pattern and color originating from the scale-like particles can be obtained.
[0029] In the present invention, the base color scaly particles (d1) (hereinafter referred to as "(d1) component") are scaly particles of one color (one type) that exhibit the base color (base color) of the design layer, and are the component contained as the main component (the component with the highest content) in the (D) component. Examples of the (d1) component include scaly base particles that have been colored. Specific examples of the base particles include inorganic pieces such as mica, sericite, clay, talc, plate-like kaolin, barium sulfate flakes, glass flakes, alumina flakes, shell pieces, and metal pieces, as well as rubber pieces, plastic pieces, and wood pieces. The coloring treatment is not particularly limited, and examples thereof include a method of coating (or adsorbing) a colorant containing a pigment or dye on the base particles, and a method of subjecting the base particles to a firing treatment or the like. In the present invention, it is preferable to use mica (colored mica) that has been coated with a colorant. By including such a component (d1) as a main component, it is advantageous not only for the design but also for making the design layer thinner and lighter.
[0030] The "scaly particles" in the present invention are not particularly limited as long as they are scaly (thin), but are preferably particles with an aspect ratio (ratio of "minor diameter / thickness") of 1.5 to 2000 (more preferably 2 to 500, and even more preferably 3 to 100). In addition, it is preferable that the ratio of the minor diameter to the major diameter (minor diameter / major diameter) is 0.3 to 1 (more preferably 0.4 to 1, and even more preferably 0.5 to 1). When the size of the scaly particles satisfies the above range, the shape is easily visible and is suitable for design. Furthermore, a design layer excellent in terms of thinning and weight reduction can be formed. The "minor diameter", "major diameter", and "thickness" referred to here are calculated by placing the scaly particles stably on a horizontal surface and observing them from above with a microscope, with the length of the shortest part being the "minor diameter", the length of the longest part being the "major diameter", and the maximum height from the bottom being the "thickness", and are values measured with a micrometer.
[0031] The present invention is characterized in that the color difference (ΔE) between the base layer formed by the first coating material and the component (d1) is 0.5 to 15 (preferably 1.0 to 10, more preferably 1.5 to 8). In such a case, the hue of the base layer and the component (d1) are in harmony, and a uniform hue is easily visually recognized as the base color (base color), and a laminated coating film with excellent aesthetics with little color unevenness and a sense of unity can be obtained. In particular, when the color difference (ΔE) satisfies the above range, even if the thickness (application amount) of the design layer is partially nonuniform, a laminated coating film with excellent aesthetics with little color unevenness can be obtained. On the other hand, when the color difference (ΔE) is less than 0.5, unevenness in color is likely to occur. In addition, when the color difference (ΔE) exceeds 15, the hue of the base layer and the design layer are unlikely to be in harmony, and the design may be inferior. In addition, in the present invention, it is preferable to set the color difference between the base layer and the component (d1) to the above range, based on the color of the component (d1).
[0032] On the other hand, when the color difference (ΔE) is less than 0.5, color unevenness is likely to occur. Although this mechanism of action is not limited, the design layer formed by the second coating material exhibits a design by the base color scale-like particles (d1), and subtle changes may occur depending on the degree of overlap, the viewing direction, and the environment (light irradiation conditions). In addition, in the design layer of the present invention, accent particles (d3) are scattered in the base pattern formed by the base color scale-like particles (d1). In such a coating, the base color is likely to be visually recognized as a hue different from the original color (for example, it feels low in saturation, etc.) due to the contrast effect (color contrast) between the base color and the accent color. When a base layer and a design layer with a color difference (ΔE) of less than 0.5 are laminated, it is considered that color unevenness is likely to be visually recognized due to the characteristics of such scale-like particles. Furthermore, if the color difference (ΔE) exceeds 15, the hues of the base layer and the design layer will not be well matched, and the design may be poor. In the present invention, it is preferable to set the color difference between the base layer and the component (d1) within the above range, using the color of the component (d1) as the standard.
[0033] The color difference (ΔE) is a value measured using a color difference meter, and can be calculated from the respective L*, a*, and b* values according to the following formula. <Formula>△E={(L *1 -L *2 ) 2 +(a *1 -a *2 ) 2 +(b *1 -b *2 ) 2} 0.5 During the ceremony, L *1 , a *1 , b *1 are the base layer L * , a * , b * . L *2 , a *2 , b *2 are the L of the (d1) component, respectively. * , a * , b * . The L*, a*, and b* values of the base layer can be calculated from the L*, a*, and b* values (average values of three or more measurement points) of the coating when the first coating material is applied to a standard white paper using a film applicator with a gap of 2 mm, the coated surface is placed horizontally, and dried for 48 hours under standard conditions (air temperature 23°C, relative humidity 50%; same below). Furthermore, the L*, a*, and b* of the (d1) component can be calculated by placing the (d1) component on a glass plate until the glass surface is covered, and then measuring the surface that is covered with a PE film (colorless and transparent).
[0034] In the present invention, in addition to the above-mentioned (d1) component, the (D) component can contain scaly particles (hereinafter referred to as (d2) component) of a similar color (approximate color) to the (d1) component. The (d2) component is a component that constitutes the base color of the design layer together with the (d1) component. The (d2) component is a color other than that exhibited by the (d1) component, and it is preferable that the color difference (ΔE) with the (d1) component is less than 2.5 (preferably more than 0 and 2.4 or less). As such a (d2) component, the same as the above-mentioned (d1) component can be used. Also, an embodiment in which the (d2) component contains two or more colors is possible.
[0035] The color differences (ΔE) of the above-mentioned components (d1) and (d2) are values measured using a color difference meter, and can be calculated from the respective L*, a*, and b* values according to the following formula. <Formula>△E={(L *3 -L *2 ) 2 +(a *3 -a *2 ) 2 +(b *3 -b *2 ) 2} 0.5 During the ceremony, L *2 , a *2 , b *2 are the L of the (d1) component, respectively. * , a * , b * . L *3 , a *3 , b*3 are the L of the (d2) component, respectively. * , a * , b * . The L*, a*, and b* of the components (d1) and (d2) can be calculated by placing the component (D) on a glass plate until the glass surface is covered, and then covering it with a PE film (colorless and transparent) and measuring the surface.
[0036] The present invention is characterized in that the component (D) contains accent particles (d3) (hereinafter also referred to as the component (d3)). The accent particles are components that are scattered in the base color pattern obtained by the above component (d1) (and the component (d2)) and impart an accent pattern. The present invention is characterized in that the component (d3) contains at least one type of particle different in type and / or color from the component (d1). This makes it possible to impart an aesthetically excellent design having an accent pattern. Examples of such a component (d3) include aggregates, luster pigments, etc., which are different types of particles from the component (d1), or scale-like particles (accent color scale-like particles) having a hue different from the component (d1). These can be used alone or in combination of two or more types.
[0037] When an aggregate is included as the (d3) component, a granular accent pattern can be imparted to the flat pattern formed by the (d1) component. As the aggregate, for example, either an organic aggregate or an inorganic aggregate can be used, and either a transparent (semi-transparent) aggregate or a colored aggregate can be used. Examples of such aggregate include crushed natural stone, ceramic powder, ceramic powder, metal particles, silica sand, feldspar, silica stone, kansui stone, glass beads, rubber particles, resin beads, etc., which may be colored. Also, aggregates having the same hue as the (d1) component can be used. The particle size of the colored aggregate is 0.01 mm to 5 mm (more preferably 0.03 mm to 4.5 mm). Furthermore, when a luster pigment is included as the component (d3), a sense of brilliance can be imparted to the pattern formed by the component (d1). Examples of the luster pigment include pearl pigments, aluminum pigments, and metallic pigments. The particle size of the luster pigment is preferably 0.5 to 100 μm (more preferably 1 to 80 μm). The particle size of the aggregate can be measured by sieving using a metal mesh sieve as specified in JIS Z8801-1:2000. The particle size of the luster pigment can be measured using a laser diffraction particle size distribution measuring device.
[0038] In the present invention, it is preferable that the (d3) component contains accent color scale-like particles (d31) (hereinafter also referred to as "(d31) component"). The (d31) component provides an accent color (accent color) for the design layer, and is dotted in the base color pattern obtained by the (d1) component (and (d2) component) to provide an accent pattern. The (d31) component is a color other than that provided by the (d1) component (and (d2) component), and the same as the (d1) component can be used. Note that the (d31) component can also be uncolored, and for example, the (d1) component's scale-like base particles can be used untreated. In addition, the (d31) component can also be in an embodiment containing two or more colors (preferably 2 to 6 colors). This allows the laminate (laminate coating) in which the base layer and the design layer are laminated to be provided with more diverse designs such as colors. In the present invention, a "different color" may be one that is different enough to be distinguishable by the naked eye, and it is preferable that the color difference ΔE from the (d1) component is 2.5 or more (more preferably 3 or more).
[0039] The color differences (ΔE) of the above-mentioned (d1) and (d31) components are values measured using a color difference meter, and can be calculated from the respective L*, a*, and b* values according to the following formula. <Formula>△E={(L *4 -L *2 ) 2 +(a *4 -a *2 ) 2 +(b*4 -b *2 ) 2} 0.5 During the ceremony, L *2 , a *2 , b *2 are the L of the (d1) component, respectively. * , a * , b * . L *4 , a *4 , b *4 are the L of the (d31) component, respectively. * , a * , b * . The L*, a*, and b* of the components (d1) and (d31) can be calculated by placing the component (D) on a glass plate until the glass surface is covered, and then covering the surface with a PE film (colorless and transparent).
[0040] The component (D) of the present invention is preferably a scaly particle (D') (hereinafter also referred to as "component (D')"). The component (D') is preferably an embodiment containing base color scaly particles (d1), and, if necessary, similar color scaly particles (d2) and / or accent color scaly particles (d31). Furthermore, the component (D') is preferably an embodiment containing large particles (L) having a short diameter of more than 2 mm (hereinafter referred to as "large particles (L)"), medium particles (M) having a short diameter of more than 0.7 mm and 2 mm or less (hereinafter referred to as "medium particles (M)"), and small particles (S) having a short diameter of 0.7 mm or less (hereinafter referred to as "small particles (S)"). By using scaly particles of different sizes in combination in this way, it is possible to form a coating film with excellent aesthetics, with a good balance (arrangement) of the pattern and little roughness, and to impart colors such as natural stone tones and designs such as large patterns.
[0041] Specifically, the large particles (L) are mainly suitable for effectively imparting a large design to the formed coating, and the present invention preferably contains large particles (L) as the (d31) component. The medium particles (M) are mainly suitable for forming the base pattern (base color) of the formed coating, and the present invention preferably contains medium particles (M) as the (d1) component (and optionally the (d2) component). The small particles (S) are suitable for imparting a small design to the formed coating and for imparting hiding properties to the formed coating, and the present invention preferably contains small particles (S) as one or more selected from the (d1), (d2) and (d31) components (preferably one or more selected from the (d1) and (d2) components).
[0042] In the present invention, it is preferable to use the large particles (L), the medium particles (M), and the small particles (S) in combination at a specific weight ratio, and it is preferable that the weight ratio [(M)+(S)] / (L) of the medium particles (M) and the small particles (S) to the large particles (L) is 1 or more and 50 or less (more preferably 3 or more and 40 or less, and even more preferably 5 or more and 30 or less). When such a range is satisfied, the large particles (L) are less likely to be biased, and a coating having excellent aesthetics and a good balance (arrangement) of the large pattern by the large particles (L) can be formed in the base pattern formed by the medium particles (M) and the small particles (S). Furthermore, the medium particles (M) and the small particles (S) can suppress the end jumping of the large particles (L), and a flat coating with little roughness can be formed. Furthermore, the weight ratio (M) / (S) of the medium particles (M) to the small particles (S) is preferably 1 or more and 30 or less (more preferably 1.5 or more and 20 or less, and further preferably 2 or more and 10 or less).
[0043] When this range is satisfied, the above-mentioned effects can be further enhanced. The mechanism of action by which such an effect is obtained is not limited, but for example, the medium particles (M) and small particles (S) smaller than the large particles (L) act as spacers for the large particles (L) and contribute to the dispersibility of the large particles (L). In addition, the small particles (S) smaller than the medium particles (M) act as spacers for the medium particles (M) and contribute to the dispersibility of the medium particles (M). As a result, it is presumed that the (D') component dispersed in the coating material can maintain good dispersibility for the large particles (L), medium particles (M), and small particles (S). In particular, it is presumed that in a coating material containing a relatively large amount of medium particles (M), the large particles (L) and the small particles (S) are dispersed in a balanced manner in the medium particles (M). It is presumed that by applying such a coating material, the particles are less likely to be biased, a coating with a well-balanced pattern is formed, and the jumping up of the particle ends can be sufficiently suppressed.
[0044] As mentioned above, the minor axis of component (D') in the present invention refers to the length of the shortest part when the scale-like particles are stably placed on a horizontal surface, but the large particles (L), medium particles (M), and small particles (S) can be classified by sieving using a metal mesh sieve (standard sieve) specified in JIS Z8801-1:2000. In this case, if the opening of the standard sieve is "a", the length of the diagonal line "L = √2a" can be considered to correspond to the minor axis. Specifically, 100 g of component (D') is weighed out and sieved for 10 minutes using a test method (manual sieving) in accordance with JIS K 0069, Large particles (L) are particles that do not pass through a 12 mesh (a=1.4mm, L=2.0mm) sieve. - Those that pass through a 12 mesh (a=1.4mm, L=2.0mm) sieve but do not pass through a 30 mesh (a=0.5mm, L=0.7mm) sieve are called medium particles (M), Those that pass through a 30 mesh (a=0.5mm, L=0.7mm) sieve are small particles (S), Let us assume that. The upper limit of the large particles (L) is preferably those that pass through a 6.5 mesh (a=2.8 mm, L=4.0 mm) sieve (particles with a minor axis of 4 mm or less), whereas the lower limit of the small particles (S) is preferably those that do not pass through a 70 mesh (a=0.21 mm, L=0.3 mm) sieve (particles with a minor axis of more than 0.3 mm).
[0045] In the present invention, the above-mentioned (D) component is preferably contained in an amount of 5 to 200 parts by weight (more preferably 10 to 100 parts by weight, and even more preferably 15 to 80 parts by weight) relative to 100 parts by weight of the solid content of the above-mentioned (A) component. The content of the (d1) component contained as a main component in the (D) component is preferably 40 to 100% by weight (more preferably 45 to 98% by weight, and even more preferably 50 to 97% by weight) relative to the total amount of the (D) component. In such a case, the (d1) component can be sufficiently visually recognized as the base color of the second covering material (design layer), and a coating film having excellent aesthetics and a homogeneous color tone can be formed. The content of components other than the (d1) component is preferably 0 to 60% by weight (more preferably 2 to 55% by weight, and even more preferably 3 to 50% by weight) relative to the total amount of the (D) component. Among these, the content of the (d2) component (total in the case of multiple colors) is preferably 0 to 50% by weight (more preferably 0 to 40% by weight) relative to the total amount of the (D) component. The content of component (d3) (total when multiple colors are used) is preferably 1 to 60% by weight (more preferably 1.5 to 50% by weight) based on the total amount of component (D). However, in components (d2) and (d3), the content of one color (one type) of scaly particles (or aggregates, etc.) is less than the content of component (d1). In such a case, the accent pattern of component (d3) is well-balanced in the base color formed by components (d1) and (d2), and a coating having a design such as a natural stone look can be obtained.
[0046] The second coating material of the present invention can be produced by uniformly mixing the above-mentioned components by a known method, but if necessary, other components that can be used in normal coating materials can also be mixed in. Examples of such components include color pigments, extender pigments, fibers, film-forming assistants, thickeners, leveling agents, coupling agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, antifoaming agents, UV absorbers, light stabilizers, antioxidants, water, etc.
[0047] The coating material of the present invention is preferably an aqueous coating material. The pH of the coating material is preferably 7 to 12 (more preferably 7.5 to 11). In such a range, the effect of the present invention can be sufficiently enhanced. Furthermore, the non-volatile content of the coating material is preferably 10 to 80% by weight (more preferably 15 to 70% by weight). In such a range, it is possible to easily form designs such as the diverse colors unique to natural stone, and to obtain a formed coating film with less roughness and more excellent aesthetics. The non-volatile content can be adjusted by adjusting the compounding ratio of each component, etc.
[0048] <Film formation method> The coating film forming method of the present invention is characterized in that a first coating material and a second coating material are applied to a substrate in this order. For example, (1) applying a first coating material to a substrate to form a base layer; (2) A step of applying a second covering material onto the base layer to form a design layer; and the like.
[0049] The substrate constitutes the surface of buildings, civil engineering structures, etc. Examples of such substrates include concrete, mortar, siding boards, extrusion molding boards, gypsum boards, slate boards, perlite boards, plywood, bricks, plastic boards, metal boards, glass, porcelain tiles, etc. These substrates may have a coating already formed on their surface, or may have wallpaper attached thereto, etc.
[0050] In the above step (1), before applying the first coating material, the substrate may be subjected to a surface treatment, if necessary. Examples of the surface treatment include a filler treatment, a putty treatment, a surfacer treatment, a sealer treatment, etc.
[0051] The first coating material in (1) above is the first coating material described above. The first coating material can be applied by, for example, spray coating, roller coating, trowel coating, brush coating, or a combination of these methods.
[0052] The first coating material can be applied once or multiple times. The first coating material is preferably applied once or twice (more preferably twice). The amount of the first coating material applied is preferably 0.05 to 1 kg / m per application. 2 (More preferably 0.1 to 0.8 kg / m 2 By applying the first coating material under such conditions, a base layer suitable for application of the second coating material can be formed, making it easier to obtain the effects of the present invention.
[0053] When applying the first coating material, a diluent such as water can be mixed to adjust the viscosity as appropriate. The dilution ratio is preferably 0 to 20% by weight. The viscosity of the first coating material to be applied is preferably 3 to 30 Pa·s (more preferably 4 to 20 Pa·s), and the thixotropy index is preferably 2 to 9 (more preferably 3 to 8). The viscosity and thixotropy index referred to here are values obtained using a BH type viscometer as a measuring instrument (measurement temperature 23°C). The viscosity is a measured value when the rotation speed is 20 rpm. The thixotropy index is a value obtained by dividing the measured value at a rotation speed of 2 rpm by the measured value at a rotation speed of 20 rpm.
[0054] The first coating material may be dried preferably at room temperature (0 to 40° C.). When the first coating material is applied multiple times, it is desirable to apply the subsequent first coating material after the coating of the previous first coating material has dried.
[0055] In the above step (2), a second coating material is applied on the base layer formed in the above step (1) to form a design layer. The above-mentioned second coating material is used as the second coating material. The second coating material can be applied by, for example, spray coating, roller coating, trowel coating, brush coating, etc. In the present invention, spray coating and roller coating are preferred, and it is particularly preferred to form a coating by spray coating using a spray. This makes it possible to easily form a coating that is flat and has excellent appearance, with a good balance (arrangement) of the pattern and little roughness, and with little unevenness of the colored particles (D). Furthermore, in the case of the scaly particles (D'), it is possible to easily form a coating that is flat and has excellent appearance, with a good balance (arrangement) of the pattern and little roughness, and with little unevenness of the scale-like particles ((d1), (d2), (d31)).
[0056] The amount of the second coating material of the present invention to be applied is not particularly limited, but is preferably 0.05 to 1 kg / m per application. 2 (More preferably 0.1 to 0.8 kg / m 2 The number of times of application can be set depending on the desired design, but is preferably 1 to 2 times (more preferably 2 times). In such a case, the effect of the present invention can be fully exhibited.
[0057] When applying the second coating material, the viscosity can be adjusted appropriately by mixing a diluent such as water. The dilution ratio is preferably 0 to 20% by weight. The viscosity of the second coating material to be applied is preferably 1 to 50 Pa s (more preferably 2 to 40 Pa s), and the thixotropy index is preferably 3 or more (even more preferably 3.5 to 15).
[0058] The second coating material may be dried preferably at room temperature (0 to 40° C.). When the second coating material is applied multiple times, it is desirable to apply the subsequent second coating material after the previous coating film of the second coating material has dried.
[0059] The present invention is characterized in that the color difference (ΔE) between the base layer formed in the above step (1) and the base-colored scaly particles (d1) contained in the second coating material in the above step (2) is 0.5 to 15 (preferably 1.0 to 12, more preferably 1.5 to 10). In such a case, a coating film exhibiting uniform color and excellent aesthetic appearance can be obtained. If the color difference (ΔE) is less than 0.5, there is a risk of unevenness in the pattern and color formed. Also, if the color difference (ΔE) is more than 15, there is a risk of the hue of the base layer being conspicuous and the design being poor.
[0060] In the coating film forming method of the present invention, a clear layer can be provided by applying a clear coating material to the outermost surface (on the design layer) for the purpose of surface protection, improving weather resistance, stain resistance, etc., as long as the effects of the present invention are not impaired. Such a clear layer may be either colorless and transparent or colored and transparent, and may be either glossy or matte (including 70% gloss, 50% gloss, 30% gloss, etc.).
[0061] <Laminate> The laminate of the present invention is a laminate having a laminate coating in which a base layer and a design layer are laminated in order on a substrate. The substrate described above is used as the substrate. The base layer is formed by the first coating material described above, and the design layer is formed by the second coating material described above. This laminate (laminate coating) is a laminate in which the design layer is laminated on the entire surface of the base layer, and the base layer can be visually recognized through the gaps between the colored particles (D) that form the design layer. The laminate of the present invention is characterized in that the color difference (ΔE) between the base layer and the base color scale-like particles (d1) contained in the design layer is 0.5 to 15 (preferably 1.0 to 12, more preferably 1.5 to 10). In such a case, an accent pattern in which the accent particles (d3) are scattered in the base pattern formed by the base color scale-like particles (d1) is formed, and a design layer with a uniform feel and less unevenness in the pattern and color originating from the scale-like particles can be obtained. If the color difference (ΔE) is less than 0.5, there is a risk of unevenness in the pattern and color formed. If the color difference (ΔE) exceeds 15, the hue of the base layer becomes conspicuous, and the design may be deteriorated. EXAMPLES
[0062] The following examples will clarify the features of the present invention.
[0063] <Manufacture of the first coating material> The following white coating materials W1 to W3 were prepared, and then each color pigment (black, yellow, red, etc.) was added to tone them to the hues shown in Table 1 to obtain first coating materials 1 to 7. (White covering material W1) White coating material 1 was prepared by mixing 200 parts by weight of acrylic silicone resin emulsion (solid content: 50% by weight, medium: water) with 60 parts by weight of titanium oxide, 200 parts by weight of powder component [silica powder with particle diameter of 20 to 400 μm (content of particle diameter of 53 to 300 μm: 75% by weight)], and additives (thickener, dispersant, defoamer, film-forming aid, etc.) in a conventional manner. (White coating material W2) A white coating material W2 was prepared in the same manner as the white coating material 1, except that a silica powder having a particle size of 20 to 400 μm (content of particles having a particle size of 53 to 300 μm: 45% by weight) was used as the powder component. (White covering material W3) A white coating material W3 was prepared in the same manner as the white coating material 1, except that calcium carbonate (particle size: 20 to 38 μm) was used as the powder component.
[0064] [Table 1]
[0065] <Manufacture of the second coating material> Based on the formulation shown in Table 2, acrylic resin emulsion (solid content 50% by weight, medium: water), colored particles (D) and additives (thickener, defoamer, film-forming aid, UV absorber, etc.) were mixed in a conventional manner to produce second coating materials 1 to 14. The colored particles (D) were prepared by mixing the scaly particles (D') in advance according to the formulation shown in Table 3. The (D') component was sieved to calculate [(M)+(S)] / (L) and (M) / (S).
[0066] (D) Colored particles (D1): Light gray mica piece [Minor diameter: over 0.3 mm and less than 2 mm, Minor diameter / Major diameter (average): 0.89, Minor diameter / Thickness (average): 10.5, L value = 88.8, a value = -0.9, b value = 4.4] (D2): Light gray mica pieces [Minor diameter: over 0.3 mm and less than 2 mm, Minor diameter / Major diameter (average): 0.89, Minor diameter / Thickness (average): 10.5, L value = 88.5, a value = -0.9, b value = 5.5] (D3): Light gray mica pieces [Minor diameter: over 1mm to 4mm, minor diameter / major diameter (average): 0.89, minor diameter / thickness (average): 10.5, L value = 88.8, a value = -0.9, b value = 4.4] (D4): Yellow mica pieces [Minor diameter: over 1mm to 4mm, minor diameter / major diameter (average): 0.88, minor diameter / thickness (average): 11.5, L value = 86.7, a value = 0.7, b value = 14.1] (D5): White mica piece [Minor diameter: over 1mm to 4mm, minor diameter / major diameter (average): 0.94, minor diameter / thickness (average): 11.0, L value = 91.5, a value = 0.5, b value = 4.4] (D6): Yellow mica pieces [Minor diameter: over 0.3 mm and less than 2 mm, Minor diameter / Major diameter (average): 0.92, Minor diameter / Thickness (average): 10.7, L value = 88.7, a value = 0.6, b value = 14.3] (D7): Gray mica pieces [Minor diameter: over 0.3 mm and less than 2 mm, minor diameter / major diameter (average): 0.87, minor diameter / thickness (average): 15.5, L value = 69.3, a value = -0.7, b value = 0.2]
[0067] [Table 2]
[0068] [Table 3]
[0069] (Examples 1 to 7, Comparative Examples 1 to 2) The first coating material was applied to the substrate (slate board: 45 x 30 cm) at a rate of 0.3 kg / m 2 Then, the second coating material was sprayed onto half of the surface with a spray gun (diameter: 5.5 mm) at a coating amount of 0.5 kg / m2. 2 The remaining half was sprayed with 0.8kg / m 2 The laminated coating was formed by spraying and drying at 23°C for 24 hours. The combination of the first and second coating materials is shown in Table 4.
[0070] <Evaluation> The following evaluations were carried out, and the results are shown in Table 4. Aesthetics The laminates with different coating amounts were visually observed and evaluated for aesthetics. The evaluation criteria were A>B>C>D, with "A" being a uniform color regardless of the viewing direction (angle) and "D" being a color with unevenness.
[0071] [Table 4]
[0072] In Examples 1 to 7, a laminated coating film having excellent aesthetics was obtained in which the (d3) component was scattered in a pattern layer having a uniform color formed by the (d1) component. In particular, in Examples 1, 2, and 5, a laminated coating film having excellent aesthetics was obtained in which the (d3) component was scattered in a pattern layer having a uniform color regardless of the viewing direction (angle). On the other hand, in Comparative Example 1, the parts with different coating amounts were visually recognized as different colors, resulting in color unevenness. Also, in Comparative Example 3, the harmony of the hues of the base layer and the design layer was poor.
[0073] (Examples 2, 8 to 17) A laminated coating was formed in the same manner as in Example 1. The combinations of the first coating material and the second coating material are shown in Table 5.
[0074] <Evaluation> The following evaluations were carried out, and the results are shown in Table 5. Aesthetics The aesthetics were evaluated in the same manner as above. ·Design Those with little bias in the scale-like particles and a well-balanced pattern were given an "AA" rating, while those with a poorer pattern were given a "D", and the evaluation was on a five-level scale from AA>A>B>C>D. Texture (touch) The coating that was formed was rated as "AA" if it had a minimal roughness, and "D" if it had a roughness, and the evaluation was based on a five-level scale of AA>A>B>C>D.
[0075] [Table 5]
[0076] In Examples 2, and 8 to 17, laminated coatings excellent in appearance were obtained in which the component (d3) was scattered in a pattern layer exhibiting a uniform color formed by the component (d1). Moreover, in Examples 10 to 12, laminated coatings excellent in design (balance of the pattern of large, medium, and small particles and balance of accent particles) and texture were obtained.
Claims
1. A coating material set for forming a laminated coating, the coating material set including at least a first coating material and a second coating material, the first coating material being a coating material that forms a base layer, the second coating material being a coating material that includes a resin component and colored particles and that forms a design layer, The colored particles are scale-like particles, The scale-like particles include large particles (L) having a short diameter of more than 2 mm, medium particles (M) having a short diameter of more than 0.7 mm and not more than 2 mm, and small particles (S) having a short diameter of 0.7 mm or less, The colored particles include base color scale-like particles and accent color scale-like particles, The base color scale-like particles are the color that is contained most in the colored particles, and the content of the base color scale-like particles is 40 to 95% by weight in the colored particles. the accent color scale-like particles are of one or more colors different from the base color scale-like particles, and their content in the colored particles is 5 to 60% by weight; the color difference (ΔE) between the base layer and the base color scale-like particles is 1.0 to 10; The coating material set is characterized in that the color difference (ΔE) between the base color scale-like particles and the accent color scale-like particles is 2.5 or more.
2. 2. The coating material set according to claim 1, characterized in that a weight ratio of the medium particles (M) and small particles (S) to the large particles (L), [(M) + (S)] / (L), is 1 or more and 50 or less.
3. A coating forming method for applying a first coating material and a second coating material in this order to a substrate, the first coating material being a coating material that forms a base layer, the second coating material being a coating material that contains a resin component and colored particles and that forms a design layer, The colored particles are scale-like particles, the scale-like particles include large particles (L) having a short diameter of more than 2 mm, medium particles (M) having a short diameter of more than 0.7 mm and not more than 2 mm, and small particles (S) having a short diameter of 0.7 mm or less; the colored particles include base color scale-like particles and accent color scale-like particles; The base color scale-like particles are the color that is contained most in the colored particles, and the content of the base color scale-like particles is 40 to 95% by weight in the colored particles. the accent color scale-like particles are of one or more colors different from the base color scale-like particles, and their content in the colored particles is 5 to 60% by weight; the color difference (ΔE) between the base layer and the base color scale-like particles is 1.0 to 10; The coating forming method is characterized in that the color difference (ΔE) between the base color scale-like particles and the accent color scale-like particles is 2.5 or more.
4. 4. The method for forming a coating film according to claim 3, wherein a weight ratio of the medium particles (M) and small particles (S) to the large particles (L), [(M) + (S)] / (L), is 1 or more and 50 or less.
5. A laminate comprising a base layer and a design layer laminated in this order on a substrate, the base layer being formed of a first coating material, the design layer being formed of a second coating material containing a resin component and colored particles, The colored particles are scale-like particles, the scale-like particles include large particles (L) having a short diameter of more than 2 mm, medium particles (M) having a short diameter of more than 0.7 mm and not more than 2 mm, and small particles (S) having a short diameter of 0.7 mm or less; the colored particles include base color scale-like particles and accent color scale-like particles; The base color scale-like particles are the color that is contained most in the colored particles, and the content of the base color scale-like particles is 40 to 95% by weight in the colored particles. the accent color scale-like particles are of one or more colors different from the base color scale-like particles, and their content in the colored particles is 5 to 60% by weight; the color difference (ΔE) between the base layer and the base color scale-like particles is 1.0 to 10; A laminate characterized in that the color difference (ΔE) between the base color scale-like particles and the accent color scale-like particles is 2.5 or more.
6. The laminate according to claim 5, characterized in that the weight ratio [(M) + (S)] / (L) of the medium particles (M) and small particles (S) to the large particles (L) is 1 or more and 50 or less.
Citation Information
Patent Citations
Stone pattern finishing method
JP1983015092A
Natural stone tone coating method and natural stone tone coating composition used to this
JP1996173899A
Method for forming stone-like coating film
JP2000265088A
Coating for forming multicolor pattern
JP2000309729A
Composition for coloring aggregate, colored aggregate and outer coated plate with clear finish
JP2004149776A